Effects of sugammadex on activated partial thromboplastin time and prothrombin time in healthy subjects - De Kam, Pieter-Jan; Grobara, Peter; Prohn, Marita; Höppener, Floris; Kluft, Cornelis; Burggraaf, Jacobus; Langdon, Ronald B; Peeters, Pierre (International journal of clinical pharmacology and therapeutics, 2014)
To assess the impact of sugammadex on activated partial thromboplastin time (APTT) and international normalized ratio for prothrombin time (PT(INR)) in healthy subjects and characterize the concentration-dependency of sugammadex effects on APTT and prothrombin time (PT) in normal human plasma in vitro. Eight healthy subjects (18 - 45 years of age) were administered intravenous doses of 4 mg/kg sugammadex, 16 mg/kg sugammadex, or placebo in a randomized, placebo-controlled, three period cross-over trial. The primary endpoint was area under the curve from 2 to 60 minutes post-dose (AUC2-60min) for APTT and PT(INR). In vitro, the effects of sugammadex on APTT and PT were assessed in pooled normal human citrate plasma. In subjects dosed with 4 and 16 mg/kg sugammadex, geometric mean ratios (treated vs. placebo) for AUC2-60min were 1.085 (95% confidence interval, 0.888 - 1.325) and 1.019 (0.868 - 1.195), respectively, for APTT, and 1.047 (0.904 - 1.213) and 1.096 (0.953 - 1.261), respectively, for PT(INR). At individual timepoints, mean APTT and PT(INR) increased by up to 22% after 16 mg/kg sugammadex compared with placebo. All such increases occurred within 30 minutes post-dose. Sugammadex was generally well tolerated. In the in vitro experiments, addition of sugammadex to plasma resulted in limited, concentration dependent increases in both APTT and PT. At 200 μg/mL (the mean maximum concentration reached therapeutically), the relative increases were 29% and 19%, respectively. Administration of sugammadex is associated with a dose-related, limited and transient prolongation of APTT and PT(INR) that is unlikely to be of clinical relevance.